Kinetics of steel casting solidification during vertical continuous casting - E. I. Marukovich; E. B. Demchenko (Литьë и металлургия, 2022)
A technique that allows calculating the values of the specific heat flux in a given range of values of the technological parameters of casting and the maximum allowable thickness of the casting crust at the outlet of the mold is proposed. The information on the temperature regime of the mold at various casting parameters can serve as a database containing the necessary information to solve the casting solidification problems. With the subsequent design of tooling and equipment, there is no need for additional experimental studies and analysis of the results obtained.